Assessment of Seismic Site Response and Liquefaction Potential for Some Sites using Borelog Data - Manish Bhutani; Sanjeev Naval (Salehan Institute of Higher Education, 2020)
Assessment of Liquefaction susceptibility of soil is very important aspect of disaster risk reduction for a particular region. The present research is an investigation to find out the liquefaction capability for the sites of Jalandhar and its surrounding region, Punjab (India) using semi empirical approach of Idris and Boulanger. Initially, the response of Ground has been analyzed with the help of DEEPSOIL software for evaluating the maximum ground acceleration values (PGASUR) at surface using five earthquake motions of magnitude, M = 6.0, 6.8 and 7.3 selected from worldwide recorded database based on seismicity of the region. The investigated PGA values ranges from 0.196 g to 0.292 g for the sites under investigation. Soil’s potential against liquefaction for 45 locations has been carried out using PGASUR results so obtained. It has been observed that eighteen sites out of forty-five are found to be susceptible to liquefaction. In order to help structural designers and geotechnical engineers for the preparation of realistic plan towards disaster risk reduction for the region, PGASUR contour map of obtained results and liquefaction hazard maps for earthquake of magnitude 6.0 and 7.0 has been prepared on geographical information system (GIS) platform using QGIS software. Doi: 10.28991/cej-2020-03091605 Full Text: PDF